1985
DOI: 10.1021/ja00311a063
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic studies on the Wolff rearrangement: the chemistry and spectroscopy of some .alpha.-keto carbenes

Abstract: Photochemical extrusion of dinitrogen from diazo ketones 1-4 matrix isolated in argon at 10-15 K produces a-ketocarbenes 5, 6, and 8. UV-vis, infrared, and electron spin resonance spectroscopy identify the -ketocarbenes, which are further characterized by trapping with carbon monoxide and dioxygen. Excitation (T0-Tt) of the -ketocarhenes leads to rapid ring contraction of 5-*9 and slow ring contraction of 6-*10 and 8-*12. This trend parallels the increasing degree of strain in the product ketenes. Shorter wave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
90
0
1

Year Published

1991
1991
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(96 citation statements)
references
References 3 publications
5
90
0
1
Order By: Relevance
“…To expand our research on transient species, we used this instrument to study the vacuum pyrolysis of 4-diazoisothiochroman-3-one (la). We anticipated that this study would add new information to the limited amount of data that are available on the vacuum pyrolysis of a-diazocarbonyl compounds in contrast to the large body of work that has been accumulated on the photochemistry of this class of compounds (4)(5)(6)(7)(8)(9)(10). Our goals were to compare the chemistries of l a and l b and establish whether two new transients, thiaketene 3a and benzocyclobutenthione (6a), that are potential products of the pyrolysis of l a could be characterized with pes.…”
Section: Methodsmentioning
confidence: 99%
“…To expand our research on transient species, we used this instrument to study the vacuum pyrolysis of 4-diazoisothiochroman-3-one (la). We anticipated that this study would add new information to the limited amount of data that are available on the vacuum pyrolysis of a-diazocarbonyl compounds in contrast to the large body of work that has been accumulated on the photochemistry of this class of compounds (4)(5)(6)(7)(8)(9)(10). Our goals were to compare the chemistries of l a and l b and establish whether two new transients, thiaketene 3a and benzocyclobutenthione (6a), that are potential products of the pyrolysis of l a could be characterized with pes.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the interaction between electronic states with different spin multiplicities, such as intersystem crossing (ISC), sometimes plays an important role in the interpretation of carbene reaction mechanisms. 1,2,11 Carbenes containing conjugated rings are of interest 3-10 because their molecular and electronic structures are very sensitive to the interaction between nonbonding electrons and the π system. Indeed, this interaction plays a role in characterizing the nature of low-lying electronic states.…”
Section: Introductionmentioning
confidence: 99%
“…The C-N=N-C dihedral angles of triplet DBH and DBO are predicted to be about 28.0 and 40. 4 o at the UB3LYP/6-31G(d) level of theory, respectively. These values somewhat decrease in their fused ring derivatives.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4] In particular, deazetization (nitrogen loss) of azoalkanes is known to be one of the important routes of formation of photochemically active azo radicals and diradicals. [5][6][7][8] Extensive studies for verifying the mechanisms of such reactions have been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation